Pembuatan Tortilla Chips Komposit Kulit Melinjo Kerikil dengan Jagung Terhadap Kualitas Inderawi, Tingkat Kesukaan Masyarakat, Kandungan Protein dan Kapasitas Antioksidan - Pangestu, Duani; Ansori, Muhammad (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2023)
The purpose of this research is to find out 1) Differences in the quality of sensory quality in terms of taste, color, aroma and texture. 2) The level of community preference. 3) Protein content and antioxidant capacity of tortilla chips different kerikil melinjo peel composites. The research method used is the prerequisite test, One Way Analysis of Variance and continued to Tukey's test if there are differences in sensory quality, the preference test uses descriptive analysis of means and Laboratory test. The results showed that there were differences in sensory quality on the color and aroma indicators of tortilla chips. Preferred test results from composite tortilla chips with kerikil melinjo peel (0%:100%, 50%:50%, 60%:40% and 70%:30%) with values (3,98, 3,86, 4,16 dan 4,03). Laboratory test results of protein content and antioxidant capacity of sample 0%:100% (6.9719%, 16.2665%), sample 50%:50% (6.6989%, 18.3361%), sample 60%:40% (7.1234%, 19.8261%), and sample (184) 70%:30% (7.3761%, 21.6887%). The conclusion is that in terms of the quality of the senses there is a significant difference in the color and aroma indicators of different composite tortilla chips of kerikil melinjo peel. The highest average preference test result is 60%: 40% sample. The highest protein content and the highest antioxidant capacity is a sample 70%:30%.